Are change of direction speed and reactive agility useful for determining the optimal field position for young soccer players? - Fiorilli, G.; Iuliano, E.; Mitrotasios, M.; Pistone, E. M.; Aquino, G.; Calcagno, G.; Di Cagno, A. (Journal of Sports Science & Medicine, 2017)
Change Of Direction Speed (CODS) and Reactive Agility (RA) are two determining factors in the ability of young soccer players. We aimed to verify if CODS and RA could be useful in order to establish the best young soccer player field position. Ninety-two elite soccer players (15.18 ± 1.21 years, weight 59.18 ± 9.93, height 1.72 ± 0.08, BMI 19.76 ± 2.22), belonging to two youth categories from the Italian First and Second Divisions, volunteered in this study. The participants included 32 defenders (15.06 ± 0.80 years), 37 midfielders (15.11 ± 0.84 years) and 23 forwards (15.48 ± 1.16 years), and they underwent two tests, each one performed in two different ways: the Y-Agility Test, carried out in a planned and reactive mode (Y-PLAN and Y-REAC), and the Illinois for Change of Direction Test (ICODT) performed with and without the ball. REAC-INDEX, which represents the index of reactivity, was calculated as Y-REAC minus Y-PLAN. The difference between the two scores of ICODT (ICODT with the ball minus ICODT without the ball) represents the TECHN-INDEX. Multivariate Analysis of Variances (MANOVA) was used to evaluate significant differences among all position groups, for all the test scores. MANOVA showed no significant differences in test scores or in TECHN-INDEX among the groups, except for the forwards, who were significantly more reactive than the defenders (p < 0.05). The strong and significant Pearson`s Correlation between ICODT with and without the ball (p < 0.01) demonstrated that physical and technical preparations have the same relevance in all positions. No significant differences were found among players in different field positions for CODS and RA performances, both with and without the ball. This study does not recommend to use RA and CODS as indicators to assign the players roles in youth soccer. Key Points: